2011
DOI: 10.1002/ece3.41
|View full text |Cite
|
Sign up to set email alerts
|

Stocks of carbon and nitrogen and partitioning between above‐ and belowground pools in the Brazilian coastal Atlantic Forest elevation range

Abstract: We estimated carbon and nitrogen stocks in aboveground biomass (AGB) and belowground biomass (BGB) along an elevation range in forest sites located on the steep slopes of the Serra do Mar on the north coast of the State of São Paulo, southeast Brazil. In elevations of 100 m (lowland), 400 m (submontane), and 1000 m (montane) four 1-ha plots were established, and above- (live and dead) and belowground (live and dead) biomass were determined. Carbon and nitrogen concentrations in each compartment were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
2
21

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 80 publications
(146 reference statements)
5
45
2
21
Order By: Relevance
“…The emissions of N 2 O decreased with altitude in the Ubatuba elevation gradient ; and at same time, an increase in the N 2 O emission was observed in warmed soils (Luiz Felipe Martins, master thesis, data not published). Finally, Vieira et al (2011) found a strong correlation with carbon and nitrogen above and below ground and soil temperature in the Ubatuba gradient. Using a regression curve between stocks and temperature, they speculated that an increase of 1 °C in mean soil temperature could result in an eventual net transfer from the forest to the atmosphere of approximately 17 Mg C ha -1 and 1.0 Mg N ha -1 .…”
Section: Potential Impacts Of Climate Change On the Carbon And Nitrogmentioning
confidence: 80%
“…The emissions of N 2 O decreased with altitude in the Ubatuba elevation gradient ; and at same time, an increase in the N 2 O emission was observed in warmed soils (Luiz Felipe Martins, master thesis, data not published). Finally, Vieira et al (2011) found a strong correlation with carbon and nitrogen above and below ground and soil temperature in the Ubatuba gradient. Using a regression curve between stocks and temperature, they speculated that an increase of 1 °C in mean soil temperature could result in an eventual net transfer from the forest to the atmosphere of approximately 17 Mg C ha -1 and 1.0 Mg N ha -1 .…”
Section: Potential Impacts Of Climate Change On the Carbon And Nitrogmentioning
confidence: 80%
“…Considerando o gradiente altitudinal, alguns trabalhos demonstraram que a biomassa aérea arbórea aumentou com a altitude em áreas de Floresta Ombrófila Densa (TIEPOLO et al, 2002;ALVES et al, 2010;VIEIRA et al, 2011). Consequentemente, estimativas apontam que o estoque de carbono nesse compartimento aumentou aproximadamente 50 Mg ha -1 ao se compararem as altitudes de 100 e 1000 m (VILLELA et al, 2012).…”
Section: Discussionunclassified
“…Estes podem ser realizados por meio do emprego de modelos matemáticos nos quais são utilizadas variáveis levantadas em inventário florestal, como diâmetro do tronco à altura do peito (1,3 m acima do solo) e/ou altura das árvores (TIEPOLO et al, 2002;VIEIRA et al, 2011). Além do compartimento vivo, o compartimento morto pode também ser considerado, com a mensuração da massa de matéria seca da camada de serapilheira disposta sobre a superfície do solo florestal (TIEPOLO et al, 2002;VIEIRA et al, 2011). Contudo, esses dados ainda são incipientes no Brasil, o que indica que estudos dessa natureza podem contribuir como estímulo à preservação de áreas não impactadas por atividades antrópicas e à recuperação de áreas já desflorestadas.…”
unclassified
“…Entretanto, considera-se que essas florestas sejam mais limitadas por fósforo do que propriamente nitrogênio (Martinelli et al 1999). Em relação à FOD Atlântica, o conteúdo de nitrogênio no solo aumentou com a altitude, provavelmente em função da queda de temperatura como indicam Vieira et al (2011).…”
Section: Comparações Florísticas Ao Longo Do Gradienteunclassified